1981
DOI: 10.1002/hlca.19810640810
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and electrical conductivity of nickel 6, 13‐di (p‐tolyl)‐5, 14‐dihydrodibenzo [b,i]‐1,4,8,11‐tetraaza [14]annulene Iodide (Ni (dtdbtaa)I2.58)

Abstract: Single crystals of the title compound are monoclinic, space group P21/n with two formula units per cell of the following dimensions: a = 18.209, b = 19.076, c = 4.075 Å, β = 92.43°. The crystals show metallic conductivity along the needle axis from room temperature down to ca. 180 K, the maximum conductivity at room temperature being 455 (Ω cm)−1. The unoxidized (iodine free) parent compound crystallizes n the monoclinic space group P21/c with 2 molecules per cell of dimensions: a = 4.988, b = 20.192, c = 11.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Interestingly, the two attached indolenine rings are coplanar with this system; thus the whole molecule (except for the methyl groups) lies in a plane [maximum deviation = 0.043(4) Å for C7], and the methyl groups lie on either side of the plane. In contrast, the planar dibenzotetraaza[14] annulenes with the meso -carbons linked to six-membered aromatic rings showed some degree of twist about the linkages. The methyl hydrogens H8C and H9C are separated from the propanediiminato H atom, H12, by 2.17 and 2.12 Å respectively, which are shorter than the van der Waals sum (2.4 Å). Selected bond lengths and angles are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the two attached indolenine rings are coplanar with this system; thus the whole molecule (except for the methyl groups) lies in a plane [maximum deviation = 0.043(4) Å for C7], and the methyl groups lie on either side of the plane. In contrast, the planar dibenzotetraaza[14] annulenes with the meso -carbons linked to six-membered aromatic rings showed some degree of twist about the linkages. The methyl hydrogens H8C and H9C are separated from the propanediiminato H atom, H12, by 2.17 and 2.12 Å respectively, which are shorter than the van der Waals sum (2.4 Å). Selected bond lengths and angles are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The nickel complexes of dibenzo[b,i]- [1,4,8,11]tetraaza [14]annulene (TAA) and 5,7,12,14-tetramethyl-dibenzo[b,i] [1,4,8,11]tetraaza [14]annulene (TMTAA), as shown below, were amongst the first to be prepared and their properties may be tailored by selective structural modification or ligation. For example, structural studies have shown that TAA complexes and analogues with methyl and aryl groups in the meso-positions, such as nickel-6,13-di(p-tolyl)-5,14-dibenzo[b,i] [1,4,8,11]tetraaza [14]annulene, [Ni II DTTAA] [2] and their Co analogues [3], and nickel-6,13-dimethyl-5, 14-dibenzo[b,i] [1,4,8,11]tetraaza [14]annulene, [Ni II DMTAA] [4] possess predominantly planar macrocyclic ring systems. In contrast, the TMTAA complexes are saddle-shaped due to the steric interaction between the methyl groups and benzene rings.…”
Section: Introductionmentioning
confidence: 99%
“…Dibenzotetraaza­[14]­annulenes are a class of synthetic macrocyclic ligands that have a planar coordination environment for a wide range of metal cations. The annulene ring is 14-membered with 16 conjugated π-electrons constituting a formally Hückel antiaromatic system. We recently synthesized the meso-substituted dibenzotetraaza[14]­annulene ([LH 2 ]) and its complexes with a number of transition metals, including Ni­(II) …”
Section: Introductionmentioning
confidence: 99%